Pengetahuan Sikap Dan Perilaku Masyarakat Terkait Mitigasi Bencana Tsunami Di Kelurahan Talise Kecamatan Mantikulore Kota Palu - Karmila; Rahmawati (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2024)
This research focused on how well the people of Talise Village are prepared to deal with a tsunami. This research aimed to assess the general awareness of tsunami preparedness in Talise Village. Using a questionnaire based on field research findings, we could gauge how prepared the local community was to deal with the aftermath of a wave. Using the Slovin formula to determine the sample size, the researcher collected data through observation, interview, survey, and documentation techniques. The researcher then used a Likert scale and data from a modified questionnaire to analyze the collected information. The overall RW knowledge results showed that the community scored between 71% and 100% under the category "very knowing," between 31% and 70% on its attitude toward tsunami disaster mitigation, making it "moderately knowledgeable," and between 0% and 30% on its behavior toward tsunami disaster management or tsunami mitigation, making it "lowly knowledgeable." The findings suggest that the people of Talise Village in Mantikulore Sun-district have a strong understanding of tsunami preparedness concepts but could use additional instruction and guidance in managing emergencies of this nature. As a result, it's crucial to educate the public at large about catastrophe preparedness. n addition, because of the precarious nature of their location, the local government must establish a warning system for tsunami catastrophes based on a consensus between officials and the community's conventional wisdom. Talise Village residents at Mantikulore Sub-district should continue educating themselves about things like the mitigation process to lessen the severity of disasters.